Історична регіоналістика VS краєзнавство: маркери дослідження мереж соціальної взаємодії в часі та просторі - Верменич, Я. (Краєзнавство, 2018)
У статті розглядається актуальність та необхідність формування дисципліноформуючого статусу краєзнавства, вироблення власного наукового інструментарію, підвищення теоретико-методологічного забезпечення краєзнавчих студій. Розглянуто когнітивний потенціал історичного краєзнавства та його дисциплінарні межі, співвідношення краєзнавства з історичною регіоналістикою. The article considers the urgency and necessity of formation of the discipline-forming status of area studies,
the development of its own scientific instruments, and the improvement of theoretical and methodological support
for local studies. The cognitive potential of historical area studies and its disciplinary boundaries, the relation
of area studies with historical regional studies is considered.
The main attention is drawn to the discussion about the definition of the subject and object of area studies,
its peculiar features and functions. It emphasizes the properties of area studies, which give him the advantages
over other forms of historical research (own methods of organization of scientific research and publication of
scientific results, corresponding institutional forms and means of dissemination of scientific knowledge). It is
noted that today national historical area studies has already taken shape in a specific social institution, a system
of professional and amateur activities, which has a certain impact on public consciousness. The concrete ways
of increasing theoretical and methodological foundations of historical area studies, its scientific and informational
potential are offered. В статье рассматривается актуальность и необходимость формирования дисциплиноформирующего статуса краеведения, выработки собственного научного инструментария, повышения теоретико-методологического обеспечения краеведческих студий. Рассмотрен когнитивный потенциал исторического краеведения и его дисциплинарные пределы, соотношение краеведения с исторической регионалистикой.